Effects of Perkinsus olseni parasitism and environmental conditions on the gonad maturation and reproductive effort of female Manila clam (Ruditapes philippinarum) on the west and south coasts of Korea - Thatchaneshkanth, S.; Hyun-Ki, H.; Kyung-Il, P.; Young-Ghan, C.; Kwang-Sik, C. (Elsevier, 2025)
In the intertidal zone, the reproductive dynamics of bivalves are influenced by both biotic and abiotic factors, including spatial and temporal fluctuations in sea surface temperature (SST), food availability, and diseases. Notably, disease proliferation is markedly enhanced under conditions favorable to pathogen entities, such as elevated SST and low food availability. This study examined the associative impacts of Perkinsus olseni parasites on the reproduction of the Manila clam Ruditapes philippinarum, across a latitudinal range covering four sampling sites along the west and south coasts of Korea, ranging approximately 400 km. In late June, we collected adult female clams to assess their condition index, reproductive output, and the prevalence of P. olseni infection. Histology indicated that 94 % of clams from SJ tidal flat, the cooler northwest coast were in the ripe stage. In contrast, clams from WD and GS, the warmer regions of the southwest and south exhibited more progressed stages of gonadal maturation, including the spent and resting phases. Notably, clams at the ripe stage in WD and GS demonstrated significantly lower gonad somatic index (GSI, P < 0.05) than their counterparts in the northwest. Moreover, the intensity of P. olseni infection was substantially higher (P < 0.05) in WD in the south compared to SJ in the northwest. The histopathological index (HPI) revealed minimal tissue damage and lower HPI scores at SJ, in stark contrast to the progressively severe tissue damage and elevated HPI scores observed moving southward along the latitudinal gradient. It was postulated that the combined effects of higher SST, low food availability, and high levels of P. olseni infection are key factors contributing to the reduced GSI and condition index (CI) in ripe clams in WD on the warm southern coast. Additionally, the lower CI observed in clams from WD potentially heightens their vulnerability to diseases by weakening their immune defenses during critical reproductive phases, such as spawning and post-spawning.
Keywords: Perkinsus olseni; Ruditapes philippinarum; Reproduction GSI; Histopathologic index; Kore